The obstructive sleep apnoea syndrome in adolescents. Issue 8 (8th August 2016) - Marcus, Carole L; Keenan, Brendan T; Huang, Jingtao; Yuan, Haibo; Pinto, Swaroop; Bradford, Ruth M; Kim, Christopher; Bagchi, Sheila; Comyn, Francois-Louis; Wang, Stephen; Tapia, Ignacio E; Maislin, Greg; et al.
Abstract : Background: The obstructive sleep apnoea syndrome (OSAS) results from a combination of structural and neuromotor factors; however, the relative contributions of these factors have not been studied during the important developmental phase of adolescence. We hypothesised that adenotonsillar volume (ATV), nasopharyngeal airway volume (NPAV), upper airway critical closing pressure (Pcrit) in the hypotonic and activated neuromotor states, upper airway electromyographic response to subatmospheric pressure and the ventilatory response to CO2 during sleep would be major predictors of OSAS risk. Methods: 42 obese adolescents with OSAS and 37 weight-matched controls underwent upper airway MRI, measurements of Pcrit, genioglossal electromyography and ventilatory response to CO2 during wakefulness and sleep. Results: ATV, NPAV, activated and hypotonic Pcrit, genioglossal electromyography and ventilatory response to CO2 during sleep were all associated with OSAS risk. Multivariate models adjusted for age, gender, body mass index and race indicated that ATV, NPAV and activated Pcrit each independently affected apnoea risk in adolescents; genioglossal electromyography was independently associated in a reduced sample. There was significant interaction between NPAV and activated Pcrit (p=0.021), with activated Pcrit more strongly associated with OSAS in adolescents with larger NPAVs and NPAV more strongly associated with OSAS in adolescents with more negative activated closing pressure. Conclusions: OSAS in adolescents is mediated by a combination of anatomic (ATV, NPAV) and neuromotor factors (activated Pcrit). This may have important implications for the management of OSAS in adolescents.